Antecedents of Digitizing ZIS Payments: A TAM and TPB Approaches - Mukhamad Yazid Afandi (Journal of Finance and Islamic Banking, 2021)
Financial technology is a form of adaptation to technological disruptions. The adoption of fintech in ZIS payments (zakat, infaq, shadaqah) is necessary if the zakat institution wants to increase fundraising from the community. This study investigates the impact of digitizing payments on interest in paying ZIS. This study uses quantitative analysis with a combined approach of the TAM and TPB. A quantitative sample was obtained from 250 respondents with 174 valid and representative questionnaires. The research areas were Yogyakarta and Surakarta. The results show that digitization of ZIS payments increases a ZIS's intention to pay. All TAM constructs, namely perceived ease of use and perceived usefulness, affect attitudes and intentions to pay ZIS. The TPB constructs namely attitude, subjective norms, and perceived behavioral control affect the intention to pay a ZIS.